2011
DOI: 10.1111/j.1445-5994.2011.02452.x
|View full text |Cite
|
Sign up to set email alerts
|

Current use of aminoglycosides: indications, pharmacokinetics and monitoring for toxicity

Abstract: The new Australian Therapeutic Guidelines: Antibiotic, version 14 have revised the recommendations for the use and monitoring of aminoglycosides. The guidelines have clear distinctions between empirical and directed therapy as well as revised recommendations about the monitoring of aminoglycosides. This has led many clinicians to review their current practice with regard to the use of aminoglycosides. This review summarizes why aminoglycosides are still a valid treatment option and discusses the rationale for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
200
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(209 citation statements)
references
References 37 publications
(52 reference statements)
0
200
0
9
Order By: Relevance
“…11 The ratio of the peak concentration to the minimum inhibitory concentration of gentamicin should be maximized to optimize efficacy. 12 This is tempered by the need to avoid excessively large areas under the concentration-time curve (AUC) to minimize the risk of toxicity. 11 For a given individual, the AUC is determined by the administered dose and the individual's gentamicin clearance.…”
Section: Introductionmentioning
confidence: 99%
“…11 The ratio of the peak concentration to the minimum inhibitory concentration of gentamicin should be maximized to optimize efficacy. 12 This is tempered by the need to avoid excessively large areas under the concentration-time curve (AUC) to minimize the risk of toxicity. 11 For a given individual, the AUC is determined by the administered dose and the individual's gentamicin clearance.…”
Section: Introductionmentioning
confidence: 99%
“…For beta-lactam antibiotics it has been shown that dose adjustment is recommended for most drugs 271 in patients with renal impairment, especially when combined with ÎČ-lactamase inhibitors [24][25][26][27][28][29][30]. 272…”
Section: Beta-lactam Antibiotics 270mentioning
confidence: 99%
“…Cmax [28] Drugs influencing renal clearance [5] LT Commonly accepted [28] Y gentamicin IV Y(R) [29], N(H)á”  tobramycin IV Y(R) [29], N(H)á”  kanamycin IV Y(R) [29], N(H) [30] amikacin IV Y(R) [29], N(H) [30] streptomycin IV Y(R) [29], N(H) [30] …”
Section: Aminoglycosidesmentioning
confidence: 99%
“…Second, antibiotic prophylaxis might have been futile in approximately half of the patients (ie, those who developed the infection >6 months after the procedure), who in fact had already received antibiotics for tackling sensitive bacteria responsible for the infection in about half of cases. The potential toxicity of aminoglycosides, 6 together with the high rate of comorbidities (including significant kidney failure) in TAVI candidates, raises caution about the universal use of such an aggressive antibiotic regimen in the absence of supportive data.…”
mentioning
confidence: 99%